Physical-chemical properties of the phenolic compounds of Humulus lupulus and aromatic plant terpenes: potential for use in a cosmetic formulation - Santos, Briolanja (2020)
The Hop (Humulus lupulus L.) are known worldwide as an essential flavor in the beer industry. Its compounds have been showing health benefits in terms ofphytochemical, pharmacological and biological profiles, due to their antimicrobial, antioxidant, anti-inflammatory and anticancer activities. This study intends todevelop a gel formulation incorporating hydroalcoholic extracts of different varieties of hops such as Cascade, Polaris and Spontaneous, from the cones and thevegetative plant parts, in different percentages. The essential oil of Thymus zygis was used as a natural conservative and the analysis of the composition was made byGC and GC-MS. Later evaluation of the physical-chemical parameters, stability and capacity to inhibit microbial growth was made. The pH measurement results of theformulations tend to be adjusted to the natural pH skin. The relative density obtained values of 1 and 0.857. It was found that there were no changes in the phase separation in the centrifugation, vibration, stability and accelerated test. However, changes were observed in the UV-Visible spectra, in texture, consistency and viscosity, and in the color test. In the light test there was phase separation in the samples, which may be related to the manufacturing technique of the formulations.However, this formulations anti aging with phenols from Hop can be development in order to obtain formulations with relevant properties for the consumers and the cosmetic industry.